Volume 3: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1992
DOI: 10.1115/92-gt-115
|View full text |Cite
|
Sign up to set email alerts
|

NOx Sensitivities for Gas Turbine Engines Operated on Lean-Premixed Combustion and Conventional Diffusion Flames

Abstract: NOx exhaust emissions for gas turbine engines with lean-premixed combustors are examined as a function of combustor pressure (P), mean residence time (τ), fuel-air equivalence ratio (φ), and inlet mixture temperature (Ti). The fuel is methane. The study is accomplished through chemical reactor modeling of the combustor, using CH4 oxidation and NOx kinetic mechanisms currently available. The NOx is formed by the Zeldovich, prompt, and nitrous oxide mechanisms. The combustor is assumed to have a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
2
13
1
Order By: Relevance
“…(Leonard and Correa also conducted experiments for lower pressures and mixture inlet temperatures. Those results were modeled previously by the present authors [4].) The length of the burner, i.e., the distance from the porous-plate to the sampling point, is 11.4cm, and the burner diameter is 5cm.…”
Section: Experimental Conditionssupporting
confidence: 69%
See 3 more Smart Citations
“…(Leonard and Correa also conducted experiments for lower pressures and mixture inlet temperatures. Those results were modeled previously by the present authors [4].) The length of the burner, i.e., the distance from the porous-plate to the sampling point, is 11.4cm, and the burner diameter is 5cm.…”
Section: Experimental Conditionssupporting
confidence: 69%
“…Combustion stabilization is then accomplished by including one or more recycle zones, by which hot, burnt gases are brought forward to the initial plug-flow reactor stage. In a previous study of leanpremixed combustion for gas turbine engines [4], this variation was found to cause little change in the NOx compared to that predicted by the baseline model, and thus, is not reconsidered herein.…”
Section: Chemical Reactor Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…6) the slightly lower calculated NO level results rather from too low formation rates worked out by the Miller-Bowman reaction mechanism than from a non-ideal PFR flow. A similar observation was made by Nicol et al (1992), who noticed an underprediction of NO for temperatures below 1800 IC by actual kinetic mechanisms.…”
Section: Nitrogen Free Fuelssupporting
confidence: 83%